The auxiliary [4Fe–4S] cluster of the Radical SAM heme synthase from Methanosarcina barkeri is involved in electron transfer. Issue 7 (15th April 2016) - Kühner, Melanie; Schweyen, Peter; Hoffmann, Martin; Ramos, José Vazquez; Reijerse, Edward J.; Lubitz, Wolfgang; Bröring, Martin; Layer, Gunhild
Abstract : The heme synthase AhbD catalyzes the oxidative decarboxylation of two propionate side chains of iron-coproporphyrin III to the corresponding vinyl groups of heme during the alternative heme biosynthesis pathway. Abstract : The heme synthase AhbD catalyzes the oxidative decarboxylation of two propionate side chains of iron-coproporphyrin III to the corresponding vinyl groups of heme during the alternative heme biosynthesis pathway occurring in sulfate-reducing bacteria and archaea. AhbD belongs to the family of Radical SAM enzymes and contains two [4Fe–4S] clusters. Whereas one of these clusters is required for substrate radical formation, the role of the second iron–sulfur cluster is not known. In this study, the function of the auxiliary cluster during AhbD catalysis was investigated. Two single cluster variants of AhbD from M. barkeri carrying either one of the two clusters were created. Using these enzyme variants it was shown that the auxiliary cluster is not required for substrate binding and formation of the substrate radical. Instead, the auxiliary cluster is involved in a late step of AhbD catalysis most likely in electron transfer from the reaction intermediate to a final electron acceptor. Moreover, by using alternative substrates such as coproporphyrin III, Cu-coproporphyrin III and Zn-coproporphyrin III for the AhbD activity assay it was observed that the central iron ion of the porphyrin substrate also participates in the electron transfer from the reaction intermediate to the auxiliary [4Fe–4S] cluster. Altogether, new insights concerning the completely uncharacterized late steps of AhbD catalysis were obtained.